Pengaruh Model Pembelajaran Berbasis Konstruktivistik dan Kemampuan Spatial Visualization Terhadap Kompetensi Menggambar Proyeksi Orthogonal - R. Mursid (JTP - Jurnal Teknologi Pendidikan, 2016)
The purpose of this study to find out: (1) whether there are differences in competency draw orthogonal projection (MPO) between the students taught using problem based learning (PBL) and taught using discovery learning (DL); (2) whether there is a difference between the competence of MPO students who have the ability of spatial visualization (KSV) which has KSV high and low; and (3) whether there is an interaction effect between constructivist learning models to competence MPO students. The research method using a quasi- experimental design with a 2x2 factorial study, while data analysis techniques using ANOVA two paths at the significance level ï¡ = 0.05. The results showed that: (1) the competence of MPO students taught by PBL model of superior competence MPO model DL; (2) competence MPO students who have high KSV superior competence MPO KSV students who have low; and (3) there are significant interaction between constructivist learning models and KSV against MPO competence of students.